2020
DOI: 10.1161/jaha.120.017624
|View full text |Cite
|
Sign up to set email alerts
|

Baseline ECG and Prognosis After Transcatheter Aortic Valve Implantation: The Role of Interatrial Block

Abstract: Background The clinical significance of conduction disturbances after transcatheter aortic valve implantation has been described; however, little is known about the influence of baseline ECGs in the prognosis of these patients. Our aim was to study the influence of baseline ECG parameters, including interatrial block (IAB), in the prognosis of patients treated with transcatheter aortic valve implantation. Methods and Results The BIT (Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…We read with great interest the study of Russo et al 1 regarding the prognostic role of interatrial block (IAB) among hospitalized COVID‐19 patients. Although the prognostic role of IAB has been previously described in several settings, 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 this is the first report regarding the association of IAB with a poor prognosis in COVID‐19. The authors found that advanced IAB was an independent predictor of thrombotic events but did not include the data regarding patients with baseline atrial fibrillation.…”
mentioning
confidence: 77%
“…We read with great interest the study of Russo et al 1 regarding the prognostic role of interatrial block (IAB) among hospitalized COVID‐19 patients. Although the prognostic role of IAB has been previously described in several settings, 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 this is the first report regarding the association of IAB with a poor prognosis in COVID‐19. The authors found that advanced IAB was an independent predictor of thrombotic events but did not include the data regarding patients with baseline atrial fibrillation.…”
mentioning
confidence: 77%
“…In recent years, aIAB has been reported for other populations as well, such as patients treated with transcatheter aortic valve implantation (12%) [33], patients with ST-elevation myocardial infarction (6%) [34] or takotsubo cardiomyopathy (5%) [35], patients with human immunodeficiency virus (4%) [36], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Several P-wave parameters on the surface electrocardiogram, particularly "interatrial block," are good predictors of AF [17,18]. In elderly patients enrolled in the PRE-DICTOR study, interatrial block strongly predicted AF indicating more than triple the risk [19].…”
Section: Discussionmentioning
confidence: 99%